BIODIVERSITY OF MARINE LIGNICOLOUS FUNGI FROM MANGROVES OF SULU SEA - Awaluddin, Hanna Hazirah; Mohamad Nor, Norlailatul Asikin; Mohamed Nor, Hanzalah; Sharuddin, Siti Sarah; Pang, Ka-Lai; Mohamad-Fauzi, Nuradilla; Rizman-Idid, Mohammed; Alias, Siti Aisyah (Malaysian Journal of Science, 2015)
Jambongan, Mandidarah and Malawali Islands in the Sulu Sea were chosen for studying marine manglicolous fungi in 2009. Driftwood, prop roots, pneumatophores, subterranean roots, rhizomes, overhanging branches and twigs of mangrove trees were examined for the presence of marine fungi. A total of 173 samples yielded 78 marine manglicolous taxa: 66 Ascomycota, 17 anamorphic morphs and one Basidiomycota. Based on percentage occurrence, the dominating taxa at Jambongan Island were Aniptodera sp. (27.5%), Sphaerulina oraemaris (24.1%) and Rhizophila marina (17.2%); Mandidarah Island were Trichocladium alopallonellum (33.3%) and Pleospora sp. 1 (13.3%) and Sphaerulina orae-maris (11.7%); and Malawali Island were Savoryella lignicola (36.4%) and Halorosellinia oceanica (20.0%). Based on Shannon Diversity Index, Jambongan Island harboured the highest diversity of marine manglicolous fungi (3.15), followed by Malawali Island (2.95) and Mandidarah Island (2.87). Sorenson Similarity Index showed that the species composition between the three study sites were dissimilar. Twelve new records of marine fungi were documented in this study which warrants further study in the area. Keywords: Manglicolous,marine fungi,occurrence,species composition